Virtual Signage – Case Study for Caminho das Capelas - MG (Research, Society and Development, 2022)
The demand for leisure in open and isolated spaces grew with the COVID-19 pandemic. With the relaxation of health regulations, this growth had an exponential increase, especially walking on pre-defined pilgrimage trails. In this context, users take the opportunity to connect with nature and especially with their religion and culture. A problem with these trails is their signage, where users are often in doubt about which way to go, as the signposts are destroyed. In this way, this destruction leaves residues, causing unsustainable tourism. Faced with this difficulty, a solution is the use of technologies to support this signage and planning, in order to obtain a more sustainable and waste-free tourism. Given the above, this work aims to develop an application for mobile devices, where there will be virtual signposts for the Caminho das Capelas, a 75km route that passes through the city of Inconfidentes-MG. However, the application is able to perform the user's location, using the telephone network (4G) associated with GNSS, or just by GNSS, in addition to presenting navigation signals. The results obtained indicate that the averages of the distances at which the application sends notifications are statistically equal, that is, that the application is able to guide the user through the circuit in a timely manner to take a direction in the different situations to which it will be exposed.